(x-a) (x-b) (x-c) (x-d)-…(x-y)(x-z) =?​

Question

(x-a) (x-b) (x-c) (x-d)…….(x-y)(x-z) =?​

in progress 0
Eloise 2 weeks 2021-09-07T11:54:54+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-07T11:56:33+00:00

    Answer:

    0

    Step-by-step explanation:

    as we move from (x-a) to (x-z), (x-x) will come and we know that (x-x)= 0 so whole product from (x-a) to (x-z) will become 0

    0
    2021-09-07T11:56:39+00:00

    Answer:

    zero because there is x-x

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )